1994
DOI: 10.1016/0014-5793(94)01262-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenic amino acid exchange via the rBAT transporter

Abstract: A cDNA clone was isolated from rabbit renal cortex using DNA-mediated expression cloning, which caused alanine-dependent outward currents when expressed in Xenopus oocytes. The cDNA encodes rBAT, a Na-independent amino acid transporter previously cloned elsewhere. Exposure of cDNA-injected oocytes to neutral amino acids led to voltage-dependent outward currents, but inward currents were seen upon exposure to basic amino acids. Assuming one charge/alanine, the outward current represented 38% of the rate of upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 17 publications
4
36
0
Order By: Relevance
“…3 and 6B). The b 0,ϩ -like transport activity expressed by rBAT cRNA in oocytes shows hetero-exchange between L-arginine and L-leucine (3)(4)(5). This has also been suggested for this transport activity in OK cells in the present study (Fig.…”
Section: Transfection Of Rbat Antisense Results In a Specific Decreassupporting
confidence: 85%
See 3 more Smart Citations
“…3 and 6B). The b 0,ϩ -like transport activity expressed by rBAT cRNA in oocytes shows hetero-exchange between L-arginine and L-leucine (3)(4)(5). This has also been suggested for this transport activity in OK cells in the present study (Fig.…”
Section: Transfection Of Rbat Antisense Results In a Specific Decreassupporting
confidence: 85%
“…The exchange of amino acids via system b 0,ϩ -like in oocytes expressing rBAT (3)(4)(5), and also suggested for this transport activity in OK cells by the results presented here, offers an additional mechanism of accumulation for cystine and dibasic amino acids in the brush border membranes of the epithelial cells of the S3 segment of the nephron; exchange with intracellular neutral amino acids could drive the active reabsorption of cystine and dibasic amino acids. Indeed, rBAT-specific accumulation of cystine occurs in oocytes where reduction to cysteine is prevented by diamide.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…A more detailed investigation of the transport induced in oocytes by NBAT has shown that this transport is in fact an exchange transport in which uptake of a cationic amino acid is enhanced by the outward flux of neutral amino acids and uptake of a neutral amino acid is stimulated by counter-transport of a cationic substrate (41,42). It was, therefore, essential to determine whether the bimodal pattern of expression also applies to the exchange transport activity.…”
Section: Expression and Characterization Of C-terminal Truncatedmentioning
confidence: 99%